CdTe and Related Compounds; Physics, Defects, Hetero- and Nano-structures, Crystal Growth, Surfaces and Applications; Part II: Crystal Growth, Surfaces and Applications - Robert Triboulet; Paul Siffert (Amsterdam, Elsevier, 2010)
Заглавие с титульного экрана